2022
DOI: 10.33971/bjes.22.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Study the Effect of Reinforcing Kevlar Fibers with Carbon Fibers and Glass Fibers on the Performance of the Athletic Prosthetic Foot

Abstract: In this research, the mechanical properties were studied from the experimental, theoretical, and numerical aspects of the sports prosthetic foot for the purpose of providing a sporty prosthetic limb with high performance, easy to use and an appropriate financial cost to use by amputees who have lost their lower limbs (amputation below the knee) in practicing their sports activities and overcoming physical disability. The dimensions of the blades were calculated based on side profiles from European patent speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Several studies proposed advances [12], challenges [13,14], and future perspectives [15] on lower limb prosthetic technology since the insight of its mechanical behaviour is essential for their proper design, development, and customisation, to optimally meet individual requirements [16]. Different research works can be found in the literature, treating various topics, such as static analysis of prosthesis technology used in elite sport [17,18] or for running [19][20][21], in order to evaluate the stiffness characteristics [22] of blade prosthetics, or the investigation of their dynamic performance [23,24]; other studies propose the development of wearable sensors for mapping the behaviour of energy storing and returning in prosthesis [25,26], and the assessment of the influence of different composite material in the performance of athletes with prostheses [8,27,28]. Indeed, no standardised tests are currently available to achieve a full characterisation of the mechanical behaviour of the blade prosthetic in operating conditions [29].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies proposed advances [12], challenges [13,14], and future perspectives [15] on lower limb prosthetic technology since the insight of its mechanical behaviour is essential for their proper design, development, and customisation, to optimally meet individual requirements [16]. Different research works can be found in the literature, treating various topics, such as static analysis of prosthesis technology used in elite sport [17,18] or for running [19][20][21], in order to evaluate the stiffness characteristics [22] of blade prosthetics, or the investigation of their dynamic performance [23,24]; other studies propose the development of wearable sensors for mapping the behaviour of energy storing and returning in prosthesis [25,26], and the assessment of the influence of different composite material in the performance of athletes with prostheses [8,27,28]. Indeed, no standardised tests are currently available to achieve a full characterisation of the mechanical behaviour of the blade prosthetic in operating conditions [29].…”
Section: Introductionmentioning
confidence: 99%